Demitologizacja negatywnego wizerunku wilka w powieści Wilk zwany Romeo Nicka Jansa - Naplocha, Anna (Zoophilologica. Polish Journal of Animal Studies, 2020)
The article deals with the issue of refuting the negative perception of the wolf among the inhabitants of Alaska in the novel A Wolf Called Romeo by Nick Jans. The pejorative perception of the wolf’s existence has its source in the persecution of this predator that began in the 17th century. Nick Jans’ non-fiction novel relates to the seven-year coexistence of Juneau residents in Alaska with a lone, untamed wolf. This novel demythologizes stereotypical, negative beliefs about wolves. This song is an important voice on the policy of protecting wolves in Alaska and is a literary illustration of the stages of gradual change in the way people perceive wolves from a negative to an affirmative attitude.